Differential metabolites and their transcriptional regulation in seven major tea cultivars (Camellia sinensis) in China - Ting GAO; Bing-hao HOU; Shu-xian SHAO; Meng-ting XU; Yu-cheng ZHENG; Shan JIN; Peng-jie WANG; Nai-xing YE (Journal of Integrative Agriculture, 2023)
Various genetic and biochemical characteristics exist in tea plant cultivars, and they largely determine production suitability and tea quality. Here, we performed transcriptomic and metabolomic analyses of young shoots of seven tea cultivars and identified major regulatory transcription factors (TFs) for the characteristic metabolites in different cultivars based on weighted gene co-expression network analysis (WGCNA). Phenotypically, we found that ‘Tieguanyin’ (TGY) and ‘Fujian Shuixian’ (FJSX), which are suitable for oolong tea, had higher catechin contents. The metabolites of ‘Jinxuan’ (JX) were more prominent, especially the contents of phenolic acids, flavonoids, terpenes, and tannins, which were higher than those of the other six cultivars. Moreover, ‘Fudingdabai’ (FDDB), which is suitable for white tea, was rich in amino acids, linolenic acid, and saccharides. At the molecular level, hydroxycinnamoyl CoA quinate hydroxycinnamoyl transferase (HCT) (CsTGY12G0001876, and CsTGY06G0003042) led to the accumulation of chlorogenic acid in TGY. The main reason for the higher l-ascorbic acid content in FJSX was the high expression levels of L-galactono-1,4-lactone hydrogenase (GalLDH) (CsTGY13G0000389) and Myo-inositol oxygenase (MIOX) (CsTGY14G0001769, and CsTGY14G0001770), which were regulated by WRKY (CsTGY11G0001197). Furthermore, FDDB, ‘Longjing 43’ (LJ43), ‘Shuchazao’ (SCZ) and ‘Baihaozao’ (BHZ) had higher free fatty acid contents, among which MYB (CsTGY14G0002344) may be a hub gene for the regulation of palmitoleic acid accumulation. More importantly, we found that the shoots of TGY were green with purple, mainly due to the accumulation of anthocyanins and the downregulation of the Mg-protoporphyrin IX nonomethyl ester cyclase (MPEC) (CsTGY10G0001989) gene that affects chlorophyll synthesis. These results will provide a theoretical reference for tea cultivar breeding and suitability.